ChemInform Abstract: Thiophostone‐Derived Broensted Acids in the Organocatalyzed Transfer Hydrogenation of Quinolines: Influence of the P‐Stereogenicity. Issue 24 (2nd June 2014) - Ferry, Angelique; Stemper, Jeremy; Marinetti, Angela; Voituriez, Arnaud; Guinchard, Xavier
Abstract Several phosphonic acid catalysts are synthesized and tested in a model reaction.